EKSPLORASI MODEL KEUANGAN YANG INKLUSIF UNTUK MENINGKATKAN PARTISIPASI PEREMPUAN DALAM BISNIS DAN KEWIRAUSAHAAN: Keuangan Inklusif, Kewirausahaan, Perempuan, Bisnis, UKM - Kusufa, Fendiyatmi; Tanuwijaya, Sjheny; Bangu Kahi, Delvin (Jurnal Paradigma Ekonomika, 2024)
Economic improvement through financial inclusion is one effective alternative to enhance the economy of marginalized groups, especially women. The gap in financial access between male and female business actors is one of the factors that slows down prosperity. Women play a crucial role in supporting the family economy, yet the support for women does not align proportionately with the contributions of women entrepreneurs to the national economy. Many parties have started to provide affirmative programs for women entrepreneurs, although these efforts are still not strong enough and lack acceleration. The aim of the research is to promote the strengthening of affirmative access to finance for women entrepreneurs and business actors. The researcher studies inclusive financial models to enhance women's participation in business and entrepreneurship in the Malang Raya region. (Kota Malang, Kota Batu, Kabupaten Malang). This study analyzes from social, cultural, economic, and political aspects. The research method uses a quantitative research design with multiple regression analysis. The research findings indicate that adopting an inclusive accounting model, supportive policies and regulations, access to financing and capital, and participation in business networks and entrepreneurial communities partially impact women's participation in business and entrepreneurship.